John Steinbeck - unknown:::Creator::::::::::::
John Steinbeck and sister Elizabeth with other children at Del Monte Hotel beach. John Steinbeck is the third from right and sister Elizabeth, described as the 'tallest in the group, is the fifth from left. Original is in the safe.